The Phonological Variation in Pulau Rengas - Malay Dialect at Merangin District - Mac Aditiawarman; Anna Hilda (Fakultas Sastra Universitas Ekasakti, 2018)
Phonology has many variants of study which could be uses as linguistic research, as well as regional language that exist in Indonesia. So it raises to interest of writer to research one of regional language around the neighborhood. It is Pulau Rengas dialect which used by Pulau Rengas people that stay at Pulau Rengas village at Bangko Barat subdistrict, Merangin regency in Jambi province. This is a linguistic research, using descriptive methode and library research to discuss about data in a way to processing and develop it using theories, such as phonology, morphology, word formation and language change theory. The research is about change sound and phonemes that occur at Pulau Rengas dialect compare by Indonesian language. First step of writer to research Pulau Rengas dialect is collect raw data that get from informants, then grouping it. In this research, writer discuss about changes, deletion and addition phonemes in vocabularies at initial, medial and final position. According this research, writer get formulas how the sound is changing which become something unique in Pulau Rengas dialect. The uniqueness is different way of pronounciation from the Indonesian language in the same meaning